Control of wave-induced vibrations on floating production systems - Travanca, J.; Hao, Hong (Elsevier, 2017)
© 2017 Elsevier Ltd Ocean wave loading is in most cases the largest environmental force acting on offshore structures. For floating structures in particular, sea waves may induce considerable motions that the design practice must account for. This paper deals with the dynamics and vibration control of floating structures due to wave loading, with particular focus on heave motion of offshore production units. A semisubmersible model is considered. The design optimization of different structural arrangements is obtained first with the proposed simplified approaches considering the platform heave motion. Different model configurations are analysed with the purpose of mitigating the vessel vibrations, in particular the heave response. The fluid structure interaction is considered and FE-CFD techniques are employed for a comprehensive analysis of the performance of the models. The worked examples and the respective interpretation of the results shine lights on the scope and application of the structural arrangements and computation techniques presented here.